2018
DOI: 10.1049/iet-epa.2017.0714
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a magnetic gear for air‐cooled condenser applications

Abstract: In high-power industrial applications such as air-cooled condenser fans, excessive mechanical gear failures highlight a need to investigate possible alternatives. In this study, the concentric magnetic gear (CMG) is evaluated as a potential replacement for traditional mechanical gear. For a more objective comparison between the CMG and mechanical gear, a CMG is optimally designed in accordance with the performance specifications of an existing mechanical gear. The design is further refined for performance impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The indicator C T reflecting severity of cogging torque in a PM machine [106][107][108][109] is usually applied to evaluate the torque ripple in an FMMG. The value of C T is the greatest common divisor of 2P 1 (or 2P 2 ) and P 3 [110][111][112]. It can be found that an FMMG with fractional gear ratio usually has a C T much smaller than that with integer gear ratio.…”
Section: Gear Ratiomentioning
confidence: 99%
“…The indicator C T reflecting severity of cogging torque in a PM machine [106][107][108][109] is usually applied to evaluate the torque ripple in an FMMG. The value of C T is the greatest common divisor of 2P 1 (or 2P 2 ) and P 3 [110][111][112]. It can be found that an FMMG with fractional gear ratio usually has a C T much smaller than that with integer gear ratio.…”
Section: Gear Ratiomentioning
confidence: 99%
“…The finite element modelling of an FMMG can also be made simpler by selecting appropriate initial angles. Since magneto-static FE solution is usually used to model an FMMG, a common practice is to position the gear components so that the peak torque can be realized [23], which means δ g = 90 • . An easy way to realize this is to align the PM pole axis of a rotor disc with that of a modulator pole-piece and then position the PM pole axis of the other rotor disc with an offset mechanical angle of 90 • /p L,H as illustrated in Figure 8.…”
Section: The Use Of Load In Fmmg Designmentioning
confidence: 99%
“…The proposed structure overcomes the drawbacks of the previous structures and can achieve low-speed high-torque operation. Furthermore, the electric continuous variable transmission system (E-CVT) can be achieved with the proposed structure, which is useful in a broad spectrum of industry and application [41], such as hybrid electric vehicles (HEVs) [42][43][44] and marine [45].…”
Section: Introductionmentioning
confidence: 99%